Dual ground-based MAX-DOAS observations in Vienna, Austria: Evaluation of horizontal and temporal NO2, HCHO, and CHOCHO distributions and comparison with independent data sets - Schreier, Stefan F.; Richter, Andreas; Peters, Enno; Ostendorf, Mareike; Schmalwieser, Alois W.; Weihs, Philipp; Burrows, John P. (Atmospheric Environment: X, 2020)
We characterize two recently installed MAX-DOAS instruments in Vienna, Austria, and evaluate horizontal path-averaged near-surface nitrogen dioxide (NO2), formaldehyde (HCHO), and glyoxal (CHOCHO) volume mixing ratios (VMRs) over the urban area by applying a state-of-the-art retrieval approach. As Vienna is influenced by Pannonian continental climate, characterized by hot summers and cold winters, a temperature correction is introduced and applied to the NO2 differential slant column densities (DSCDs) retrieved in the visible spectral range to correct for the temperature dependence of the NO2 cross-section. The results show that not accounting for such a correction leads to an overestimation of absolute values by up to 15% in the winter season. Path-averaged NO2 VMRs from selected horizontal viewing directions are compared with surface NO2 VMRs from air quality monitoring stations located below and/or in close proximity to the particular MAX-DOAS line of sight. Good agreement between the two independent data sets is found, in particular during the summer season, with correlation coefficents ranging between 0.76 and 0.94. Seasonal and diurnal cycles of path-averaged NO2, HCHO, and CHOCHO VMRs are evaluated for a full year of measurements taken at the lowest elevation angles. While the highest daytime monthly averages of NO2 VMRs are found in winter, peaks of HCHO occur in summer. Highest amounts of CHOCHO conversely are observed over the course of the year, with the exception of summer. Seasonally-averaged diurnal cycles indicate that elevated NO2 and CHOCHO amounts are generally found in the morning hours and that there is a clear difference in trace gas amounts between weekdays and weekends when pointing at anthropogenic sources. The horizontal variabilty of tropospheric NO2, HCHO, and CHOCHO amounts is investigated by analyzing seasonally-averaged path-averaged VMRs, again obtained from measurements taken at the lowest elevation angles. The results show that highest amounts of NO2 and CHOCHO are found when the MAX-DOAS instruments are pointing towards the city center and/or towards busy roads and industrial areas, whereas highest amounts of HCHO are found over northern and western parts of Vienna, in particular in summer, which implies that anthropogenic sources are not the dominant drivers of HCHO production during that time of the year. Finally, the influence of wind direction and wind speed on tropospheric NO2, HCHO, and CHOCHO amounts is evaluted. The results show that tropospheric pollution levels over the city center of Vienna are highest at low wind speeds and wind directions from the Southeast. •Horizontal measurements of two MAX-DOAS instruments in Vienna are analyzed.•A temperature correction is applied to the NO2 differential slant column densities.•Near-surface NO2, HCHO, and CHOCHO mixing ratios are retrieved.•Highest mixing ratios are found when calm winds blow from the southeast.•Anthropogenic sources are not the dominant drivers of HCHO production in Vienna.